"Characterization of Pathogenic Variants of Mitochondrial Carriers and Transporters With the Use of Biochemical Methods: Revealing Novel Mutations and Deletions in Patient Samples, Assumed to be Associated With Rare Diseases." - Behensky, Magdalena Maria (Jihočeská univerzita, 2022)
Research concerning orphan diseases pose a challenge to the scientific community, however, they are both of great interest and great necessity, leading to the improvement of treatment opportunities for the 263 to 446 million people affected worldwide and, subsequently, their quality of life. The presence of mitochondria in virtually all kinds of cells, with the exception of mature erythrocytes, make clinical diagnosis of mitochondrial diseases extremely challenging and difficult, as dysfunction in mitochondria can affect any organ, or even whole organ systems. A major challenge for modern medical science, is the identification of the genes affected, which cause specific rare diseases in humans. New technologies, such as next-generation sequencing, and, therefore, the possibility of identifying genetic variations, are rapidly proceeding. Consequently, available treatments, or genetic counseling can be found more often. SLC25A3 is a mitochondrial phosphate-carrier responsible for the transport of inorganic phosphate into the mitochondrial matrix, which is required for the final step of oxidative phosphorylation, and the process of aerobic synthesis of ATP. Alteration in this gene, located on chromosome 12q23.1, is known to cause PiC deficiency (OMIM 610773), which affects the heart-/muscle-specific phosphate-carrier isoform A (PiC-A) [19, 23, 24, 26]. The aim of the Master's Thesis, was to ascertain the impact of the mutation on the activity of the phosphate carrier, and the patient's resulting life expectancies. Previously, three mutations have been described in seven patients, as being homozygous, affecting exon 3A, with the exception of one, which is compound heterozygous and affecting exon 4. The four novel SLC25A3 mutations (p.Gly72Glu, p.Thr81Lys, p.Asp87Tyr, p.Ala124Pro) are homozygous, one (p.Gly72Glu) having been described previously [19,26,30]. In the context of this thesis, four patient samples were used for experimentation, each containing one of these homozygous mutations. SLC19A3 encodes the thiamine transporter 2 (hTHTR2), dysfunctions lead to recurrent encephalopathy, basal ganglia necrosis, generalized dystonia, severe disability and early death. Patients with changes in SLC19A3, located on the second chromosome (q36.3), show a considerable reduction of free-thiamine in cerebrospinal fluid and fibroblasts [34]. The clinical pathology of SLC19A3 is heterogeneous, and, likely, related to the age of onset [49]. Previously, Mayr et al. [27] reported various mutations associated with a thiamine pyrophosphokinase deficiency in encephalopathic children, as well as Kevelam et al. [70], who reported mutated SLC19A3 (p.Ser181Pro, p. Leu385Arg and p.Gly23Val) in patients with an early-infantile, lethal encephalopathy. Furthermore, Schänzer et al. [60], Whitford et al. [71] and Fl?nes et al. [63] have reported bigger partial deletions in SLC19A3. Assuming a partial deletion in the sequence of one of the patient samples, the main task of the second project was the determination of the edges, the localization of the breaking point, and further, the size of the deletion, and, whether this deletion has an impact on gene activity. Additionally, the influence of the location and size of the deletion on the overall condition of the patients was analyzed. Furthermore, a sample from a patient, who was previously identified as having a complete deletion of SLC19A3, was added to the experimentation for verification purposes. Finally, the newly found partial deletion and complete deletion were compared to the previously reported deletions. Large deletions of genes are of particular interest, due to their rarity. Large partial deletions, or even complete deletions are seldomly found and reported, as they are complicated to detect, and generally very rare. As in this case, sometimes, they are only detectable when searching in the non-coding region. Therefore, it is important to search in the right places.
"Characterization of Pathogenic Variants of Mitochondrial Carriers and Transporters With the Use of Biochemical Methods: Revealing Novel Mutations and Deletions in Patient Samples, Assumed to be Associated With Rare Diseases."
Keywords: SLC25A3; rare genetic diseases; phosphate carrier; point mutation; mitochondrial diseases; PiC deficiency; SLC19A3; thiamine transporter 2; recurrent encephalopathy; basal ganglia necrosis; partial deletion; large deletion; complete deletion; SLC25A3; rare genetic diseases; phosphate carrier; point mutation; mitochondrial diseases; PiC deficiency; SLC19A3; thiamine transporter 2; recurrent encephalopathy; basal ganglia necrosis; partial deletion; large deletion; complete deletion